Collaborative Governance Model in Improving Community Economy: Optimizing Village Funds - Arma, Nur Ambia; Agusdiana, Bambang; Madya, Faizal (Universitas Teuku Umar, 2024)
One of the implementations of the Village Law policy which is a government strategy to realize independent and autonomous villages is to provide village funds as a source of income. This village fund is used 30% for operational costs of the Village Government and Village Consultative Body (BPD) and 70% for community empowerment and strengthening the capacity of the village government. The provision of village funds is one solution to the problems faced by the village through sources of income. Pematang Johar Village is one of the superior villages in Deli Serdang Regency because of the development of tourist villages. This study also aims to identify the use of village funds carried out by Pematang Johar Village to improve the economy of residents and identify the type of collaborative governance formed in supporting the use of village funds and development. They are using a descriptive qualitative research method with data collection techniques through interviews, observations, and documentation studies. Data analysis techniques include collecting data, reducing data, presenting data, and providing conclusions. The results show several things. 1) that the village government does not have a clear collaboration structure so there is no clarity regarding the roles and duties of each stakeholder. 2) Lack of active participation and initiative from the community, so it is necessary to make the community one of the collaboration partners. 3) there is no supervision and evaluation process for each program so there needs to be a unification of vision and commitment from stakeholders so that the use of village funds through empowerment programs and development of tourism villages can run sustainably and ultimately improve the community's economy.